Brand Identity and Visual Communication in Instagram Content @Course_Net: Identitas Merek dan Komunikasi Visual dalam Konten Instagram @Course_Net - Hastowo, Kiki Widyasari; Sinduwiatmo, Kukuh (Universitas Muhammadiyah Sidoarjo, 2025)
(General Background) The rapid development of technology and digital media in the Industrial Revolution 4.0 era has transformed the way information is produced and disseminated, especially through social media platforms such as Instagram. (Specific Background) The @Course_Net Instagram account represents a unique example of digital marketing integration and visual communication strategy in the IT education sector. (Knowledge Gap) However, limited studies have explored how brand identity and information systems are formed through visual and interactive communication within online learning communities. (Aims) This study aims to analyze the process of forming brand identity and the role of information systems in shaping digital interaction culture on the @Course_Net Instagram account using a netnographic approach. (Results) The findings reveal that @Course_Net successfully builds a distinctive brand identity through consistent use of minimalist design, specific color schemes, and active two-way interaction that fosters a participatory virtual community. (Novelty) This research contributes a comprehensive understanding of how visual communication and cultural interaction intersect in social media branding for digital education institutions. (Implications) The results highlight the importance of aesthetic consistency and ethical interaction in sustaining audience engagement and strengthening digital brand credibility. Highlights: Consistent visual elements strengthen brand recognition. Interactive communication fosters online community culture. Aesthetic and ethical engagement enhances brand credibility. Keywords: Brand Identity, Instagram, Netnography, Visual Communication, Digital Marketing